The aetiology of acute community acquired bacterial meningitis in children and adults in Maputo, Mozambique - Tomás F. Zimba; David T. Nota; José C. Langa; Leonel G.S. Monteiro; Yacoob M. Coovadia (Journal of Infection in Developing Countries, 2009)
Background: Community-acquired acute bacterial meningitis is a life-threatening infection and many outbreaks have been reported all around the world.